A Structural Analysis of Column Gusset Plates on the Production Module Support Structures - Ardianti, Andi; Daerobi, Muhammad Najib Sadikin; Alie, Muhammad Zubair Muis (Engineering, Technology & Applied Science Research, 2026)
Floating Production Storage and Offloading (FPSO) units are complex offshore production facilities, whose topside modules are supported by multicolumn structures. A main component of this system is the gusset plate, which connects and reinforces the joints between the columns and other structural members while distributing internal forces. Under combined static and dynamic loading, gusset plates are prone to localized deformation, which may reduce joint stiffness and compromise structural stability. This study analyzes the mechanical behavior of the gusset plates in production module support structures using numerical analysis based on the Finite Element Method (FEM). Three different gusset plate configurations were developed and compared to evaluate the influence of geometry on the stress distribution, deformation patterns, and safety factors under identical operational and environmental load cases. The results indicate that gusset geometry significantly affects stress concentration, with the Corner model exhibiting the highest Von Mises stress (647 MPa), the Round model showing moderate improvement (567 MPa), and the Flat model achieving the lowest stress (474 MPa) and the most uniform distribution. These findings highlight the importance of geometric optimization in enhancing the structural reliability and load-transfer performance of production-module support systems.